Forest Governance: Hydra or Chloris? - Arts, Bas (Physical Sciences, 2021)
Many forest-related problems are considered relevant today. This Element takes stock of these issues and initiatives by analysing different forest governance modes, shifts and norms, and case studies. This title is also available as Open Access on Cambridge Core.